Alkaloids Modulate the Functioning of Ion Channels Produced by Antimicrobial Agents via an Influence on the Lipid Host - Efimova, Svetlana S.; Zakharova, Anastasiia A.; Ostroumova, Olga S. (Frontiers in Cell and Developmental Biology, 2020)
It is widely recognized that an alteration in membrane physical properties induced by the adsorption of various drugs and biologically active compounds might greatly affect the functioning of peptides and proteins embedded in the membrane, in particular various ion channels. This study aimed to obtain deep insight into the diversity of the molecular mechanisms of membrane action of one of the most numerous and extremely important class of phytochemicals, the alkaloids. Protoalkaloids (derivatives of β-phenylethylamine, benzylamines, and colchicines), heterocyclic alkaloids (derivatives of purine, quinolysidine, piperidine, pyridine, quinoline, and isoquinoline), and steroid alkaloids were tested. We evaluated the effects of 22 compounds on lipid packing by investigating the thermotropic behavior of membrane lipids and the leakage of a fluorescent marker from unilamellar lipid vesicles. The alteration in the transmembrane distribution of the electrical potential was estimated by measuring the alkaloid induced changes in the boundary potential of planar lipid bilayers. We found that benzylamines, the chili pepper active components, capsaicin and dihydrocapsaicin, strongly affect not only the elastic properties of the lipid host, but also its electrostatics by dramatic decrease in membrane dipole potential. We concluded that the increase in the conductance and lifetime of gramicidin A channels induced by benzylamines was related to alteration in membrane dipole potential not to decrease in membrane stiffness. A sharp decrease in the lifetime of single ion pores induced by the antifungal lipopeptide syringomycin E, after addition of benzylamines and black pepper alkaloid piperine, was also mainly due to the reduction in dipole potential. At the same time, we showed that the disordering of membrane lipids in the presence of benzylamines and piperine plays a decisive role in the regulation of the conductance induced by the antifungal polyene macrolide antibiotic nystatin, while the inhibition of steady-state transmembrane current produced by the antimicrobial peptide cecropin A was attributed to both the dipole potential drop and membrane lipid disordering in the presence of pepper alkaloids. These data might lead to a better understanding of the biological activity of alkaloids, especially their action on voltage-gated and mechanosensitive ion channels in cell membranes.